2015
DOI: 10.1073/pnas.1503830112
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral idiosyncrasy reveals genetic control of phenotypic variability

Abstract: Quantitative genetics has primarily focused on describing genetic effects on trait means and largely ignored the effect of alternative alleles on trait variability, potentially missing an important axis of genetic variation contributing to phenotypic differences among individuals. To study the genetic effects on individual-to-individual phenotypic variability (or intragenotypic variability), we used Drosophila inbred lines and measured the spontaneous locomotor behavior of flies walking individually in Y-shape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
209
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(220 citation statements)
references
References 47 publications
11
209
0
Order By: Relevance
“…Behavioral variability in individuals is due to genetic, developmental, pharmacological, environmental and social processes (Kappeler and Anthes, 2010; Laskowski and Bell, 2014). Inter-individual behavioral variation is widely observed across animal phyla and might be under selective pressure during animal evolution (Ayroles et al, 2015; Laurila et al, 2008). However, variation among individuals is often ignored when behavior is quantified as averages with associated dispersions (Geiler-Samerotte et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral variability in individuals is due to genetic, developmental, pharmacological, environmental and social processes (Kappeler and Anthes, 2010; Laskowski and Bell, 2014). Inter-individual behavioral variation is widely observed across animal phyla and might be under selective pressure during animal evolution (Ayroles et al, 2015; Laurila et al, 2008). However, variation among individuals is often ignored when behavior is quantified as averages with associated dispersions (Geiler-Samerotte et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A study on variation in gene expression has shown that segregating mouse lines are instrumental to identify loci underlying within-strain variability (Fraser and Schadt 2010). In fact, a recent study using different Drosophila inbred lines confirmed the idea that different genotypes vary dramatically in their propensity for variability, and that loci affecting variability could be mapped (Ayroles et al 2015). We anticipate that systematic automated behavioral analysis panels of inbred or mutant mice in the home-cage could provide the throughput, multidimensionality and sensitivity for genetic dissection of phenotypic robustness in mice as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methods have been developed to detect QTLs that control variability, so-called vQTLs (Rönnegård and Valdar 2011; Rönnegård and Valdar 2012), and these have been found in studies of litter size in pigs (Sell-Kubiak et al 2015), several morphological traits and days to flowering in maize (Ordas et al 2008), and locomotor behavior in fruit flies (Ayroles et al 2015). Furthermore, several mechanisms, resulting in vQTL effects have been proposed (Rönnegård and Valdar 2011; Rönnegård and Valdar 2012), including: epistatic gene interaction, gene-by-environmental interaction, multi-allelic additive effects underlying a QTL and scale of measurement for the observed phenotype.…”
Section: Discussionmentioning
confidence: 99%